Clean water in the slums of East Africa! The mission of the Hungarian Charity Service of the Order of Malta (Academic Journal of Internal Affairs, 2023)
Aim: Researchers working on human security now know that all disciplines need to address the water issues of our planet, which is a major determinant of the sense of security of human life, because where there is no water, there is no life, and so there is no security. However, where there is water, but it is not of the right quality, i.e. it is not safe for biological organisms, it is still a threat. The absence of water, or its contamination can create a humanitarian crisis, a disaster or a natural disaster. The process of preventing, averting and remediating all these undesirable conditions is observed by the authors in the slums of three states in Central and Eastern Africa: Kenya, Uganda and Tanzania.Methodology: The authors have examined the historical and natural conditions of the African continent, the antecedents, possibilities and circumstances of the problem. They have explored a small body of international literature on the subject, interpreted the findings and assessments of academic literature and proposed solutions to the problem. The activities and methods of a Hungarian NGO in this field were examined.Findings: The authors of the study conclude that the African continent is facing many problems, that the slums are on the verge of a humanitarian and natural disaster, that the political systems of these states are unable or unwilling to deal with the problem, and that it is therefore necessary to call for the intervention of internal or external (international) NGOs to minimise the human cost of the humanitarian crisis.Value: It is made clear in the study that a Hungarian NGO has saved the lives of tens of thousands of children, women and elderly people in the African slums under study through its technical intervention. If public bodies cannot do it, NGOs can prevent, respond to and recover from humanitarian disasters.
Keywords: Africa; slum; humanitarian mission; clear water